Dental Erosion and Dentinal Sensitivity amongst Professional Wine Tasters in South East Queensland, Australia - Roy George; Allison Chell; Belinda Chen; Rebecca Undery; Humza Ahmed (The Scientific World Journal)
Background/Aims. Professional wine tasters face a hidden occupational hazard due to the high acid content in wine. This study evaluates the self-perceived dentinal sensitivity and erosive effects of wine on the professional wine tasters of the Granite Belt and the Scenic Rim regions of South East Queensland, Australia. Methods. Seventy wineries were contacted and participants were surveyed about their professional wine tasting experience and oral health. Participants were also required to rate their tooth sensitivity prior to being examined for erosion using a modified Smith & Knight tooth wear index. The data were analysed using Mann Whitney U test and Spearman’s correlation test. Results. The results showed that most participants (25 males, 22–66 yrs), brushed twice a day; however, the majority did not floss daily and had limited knowledge of the erosive effect of wine. There was a direct correlation between years of wine tasting, age of participants, and the erosion index. Correlation was not observed between the participant’s sensitivity index and erosion index. Conclusion. The lack of significant experience of dentinal hypersensitivity amongst professional wine tasters should not prevent oral health practitioners from providing necessary counselling and undertaking preventive measures, as tooth wear can have serious long-term effect on oral health of an individual.